Reciprocating and Rotatory NiTi Instruments Used for Root Canal Preparation of Primary Teeth: A Systematic Review and Meta-Analysis - Laura Izabel Lampert Bonzanini; Cleber Paradzinski Cavalheiro; Maitê Munhoz Scherer; Djessica Pedrotti; Paola Arosi Bottezini; Ricardo Abreu da Rosa; Luciano Casagrande; Tathiane Larissa Lenzi (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare the root canal preparation of primary teeth with reciprocating and rotary NiTi instruments. Material and Methods: Electronic databases (PubMed/MEDLINE, Web of Science, TRIP, Lilacs, Embase, and Scopus) were systematically searched until October 2020. In vitro studies comparing the cleaning ability, debris extrusion, file deformation, or working time of rotary and reciprocating NiTi instruments in primary teeth were evaluated. Two reviewers independently selected the studies, extracted the data, and assessed the risk of bias. Meta-analyses were conducted using a random-effects model to calculate pooled mean differences between reciprocating and rotary NiTi instruments considering the outcomes: working time (minutes) and debris extrusion (milligrams). Statistical analyses were performed using RevMan 5.3 at a significance level of 5%. Results: From 4,417 potentially relevant studies, 10 were included in the systematic review, and 8 considered in the meta-analyses. There was no significant difference between reciprocating and rotary NiTi instruments considering debris extrusion [3 data sets; effect size: -0.11 (-0.25-0.04); p=0.15] and working time [6 data sets; effect size: -0.37 (-0.98-0.24); p=0.24]. The heterogeneity found was moderate to high. The risk of bias was low in most studies (50.0% of all items across studies). Conclusion: There is no scientific evidence showing superiority of reciprocating or rotary NiTi instruments used for root canal preparation in primary teeth.